Analysis of Small and Medium Enterprises’ (SMEs) Sustainability Reporting to Develop Sustainability Reporting Guideline - Paulina Permatasari; Elsje Kosasih (International Journal of Entrepreneurship and Sustainability Studies, 2022)
Sustainability reporting is conducted to communicate organizations’ sustainable development contributions to their stakeholders. The sustainability reporting trend has been increasing in Indonesia for the past few years, with the government has made sustainability reporting mandatory for all public companies. In the near future, it is believed that the Government of Indonesia will also obligate small and medium-sized enterprises (SMEs) to publish sustainability reports. SMEs have significant impacts in Indonesian economy, with the number of SMEs continue to increase each year and they contributed more than half of the national GDP. So far, there are no specific guidelines for SMEs’ sustainability report. There are many indicators in the global sustainability reporting guidelines that are not suitable for SMEs since they are limited in the resources and knowledge they can disseminate. Therefore, this study aims to develop a sustainable reporting guideline for SMEs. This study analyzes the development of sustainability reporting practices in Indonesia and other countries through literature review, interviews, and surveys, in order to develop a sustainability reporting guideline for SMEs. The reporting guideline recommended in this study contains 25 indicators: 12 general information indicators, 1 economic indicator, 6 environmental indicators, and 6 social indicators. Based on a survey of 25 SMEs, this guideline is suitable for preparing SMEs’ sustainability reports.